Hydrothermal synthesis of ZnO quantum dot/KNb3O8 nanosheet photocatalysts for reducing carbon dioxide to methanol - Shao, Xiao; Xin, Weiyue; Yin, Xiaohong (Beilstein Journal of Nanotechnology, 2017)
ZnO quantum dots and KNb3O8 nanosheets were synthesized by a two-step hydrothermal method for the photocatalytic reduction of CO2 to methanol where isopropanol is simultaneously oxidized to acetone . The as-prepared photocatalysts were characterized by X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM) and UV–vis absorption spectroscopy (UV–vis). The photocatalytic activity of the materials was evaluated by formation rate of methanol under UV light irradiation at ambient temperature and pressure. The methanol formation rate of pure KNb3O8 nanosheets was found to be 1257.21 μmol/g/h, and after deposition of 2 wt % ZnO quantum dots on the surface of KNb3O8 nanosheets, the methanol production rate was found to increase to 1539.77 μmol/g/h. Thus, the ZnO quantum dots obviously prompted separation of charge carriers, which was explained by a proposed mechanism for this photocatalytic reaction.
Keywords: CO2 reduction; KNb3O8 nanosheets; methanol production; photocatalysis; ZnO quantum dots